ANALISIS METRIK KETERLIBATAN TERHADAP PERTUMBUHAN PENGIKUT AKUN INSTAGRAM ITBSS: PENDEKATAN ANALISIS STATISTIK - Melyanto Melyanto (LPPM Universitas Abdurrab, 2026)
Digital transformation has significantly changed higher education marketing. Higher Education is now competing not only in academic quality but also in marketing strategies, particularly through social media platforms such as Instagram. However, the success of marketing campaigns on Instagram needs to be measured quantitatively using available metrics such as engagement which includes likes, comments, shares, reach, and profile visit. These metrics could be used to analyze and evaluate the impact for institution brand awareness by identifying the numbers of followers’ growth. This quantitative research utilized insights data from the Institut Teknologi dan Bisnis Sabda Setia (ITBSS) Instagram account engagement metrics. Statistical analysis involved including descriptive analysis, Pearson’s correlations and regression analysis. This research found an outlier and multicollinearity between interaction and profile visit metrics. Engagement metrics have positive correlation and 58% of follower’s growth explained by engagement metrics. The F-test yielded a result of 0.19, indicating that the regression model is not yet significant in predicting follower growth. The findings are expected to assist ITBSS digital transformation by utilizing engagement metrics efficiently to increase follower’s growth. Digital transformation in Instagram usage as marketing medium for ITBSS contributes significantly through findings of a positive correlation between engagement metrics and follower growth. However, in terms of the model, it is not yet significant and requires further research in the future.